What are the concerns of second-degree medical students entering specialty OMFS training?. Issue 2 (February 2023) - Perwaiz, Ibrar; Rehman, Umar; Sarwar, Mohammad Sohaib; Brennan, Peter A.
Abstract: Oral and maxillofacial surgery (OMFS) applicants are faced with numerous challenges. Previous research has demonstrated that financial burden, length of OMFS training, and impact on personal life are cited as major drawbacks to pursuing the specialty, with trainees having concerns about the Membership of the Royal College of Surgeons (MRCS) examinations. The current study aimed to explore second-degree medical students' concerns about obtaining a specialty training post in OMFS. An online survey was distributed via social media to second-degree students across the United Kingdom and 106 responses were received. A lack of publications and lack of involvement in research (54%) as well as attaining accreditation with the Royal College of Surgeons (27%) were cited as the primary and secondary concerns in relation to securing a higher training post. Seventy-five per cent of respondents had no first-author publications, 93% expressed concerns about passing the MRCS examination, and 73% had more than 40 OMFS procedures within their logbook. Second-degree medical students reported having ample clinical and operative experience in OMFS. Their main concerns were about research and MRCS examinations. To alleviate these concerns, BAOMS could provide educational initiatives and dedicated mentorship programmes for second-degree students, and could adopt a collaborative approach with discussion with major postgraduate training stakeholders.